2014
DOI: 10.1186/1471-2334-14-148
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis among people living with HIV/AIDS in the German ClinSurv HIV Cohort: long-term incidence and risk factors

Abstract: BackgroundTuberculosis (TB) still presents a leading cause of morbidity and mortality among people living with HIV/AIDS (PLWHA), including those on antiretroviral therapy. In this study, we aimed to determine the long-term incidence density rate (IDR) of TB and risk factors among PLWHA in relation to combination antiretroviral therapy (cART)-status.MethodsData of PLWHA enrolled from 2001 through 2011 in the German ClinSurv HIV Cohort were investigated using survival analysis and Cox regression.ResultsTB was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 25 publications
2
43
1
6
Order By: Relevance
“…We observed that the majority of HIV and TB diagnoses were made simultaneously, resulting in a prominent peak in TB incidence within the first few months of HIV diagnosis. Consequently, we show TB incidence rates among HIV diagnosed to be much higher than observed in clinical HIV cohorts both in the UK26 and in other European cohorts 27…”
Section: Discussionmentioning
confidence: 45%
“…We observed that the majority of HIV and TB diagnoses were made simultaneously, resulting in a prominent peak in TB incidence within the first few months of HIV diagnosis. Consequently, we show TB incidence rates among HIV diagnosed to be much higher than observed in clinical HIV cohorts both in the UK26 and in other European cohorts 27…”
Section: Discussionmentioning
confidence: 45%
“…It has been previously shown that PLWH with lower CD4 counts are more likely to develop TB compared with people with better immune status at HIV diagnosis . Similar to data reported annually from European Centre for Disease Prevention and Control (ECDC) , we found pulmonary TB to be the most frequent clinical form of disease.…”
Section: Discussionmentioning
confidence: 97%
“…Treatment for HIV is lifelong, while TB can occur at any stage of the disease. The risk of TB increases with increased duration after seroconversion and advancement of immunosuppression 26 27. Although HIV patients not on treatment can be monitored outside the network of HIV treatment facilities in the Netherlands (although it only happens sporadically), ART is only available in these centres.…”
Section: Discussionmentioning
confidence: 99%